Long-term Safety of Living Kidney Donation in an Emerging Economy. Issue 6 (June 2016) - Rizvi, S. Adibul Hasan; Zafar, Mirza Naqi; Jawad, Fatema; Aziz, Tahir; Hussain, Zafar; Hashmi, Altaf; Hussain, Manzoor; Akhtar, Fazal; Ahmed, Ejaz; Naqvi, Rubina; Naqvi, S A Anwar
Abstract : Background: Long-term follow-up and management of donors was undertaken in a specialist kidney transplant unit in Pakistan to identify risk and prevent adverse outcomes in living related kidney donors. Methods: In an observation cohort study between 1985 and 2012, 3748 donors were offered free medical follow-up and treatment 6 to 12 months after donation and annually thereafter. Each visit included history, physical examination, blood tests for renal, lipid, glucose profiles, and 24-hour urine for proteinuria and creatinine clearance. Preventive intervention was undertaken for new onset clinical conditions. Donor outcomes were compared with 90 nondonor healthy siblings matched for age, sex, and body mass index. Results: Of the 3748 donors, 2696 (72%) were in regular yearly follow-up for up to 27 years (median, 5.6; interquartile range, 7.9). Eleven (0.4%) died 4 to 22 years after donation with all-cause mortality of 4.0/10 000 person years. Six (0.2%) developed end-stage renal disease 5 to 17 years after donation, (2.7/10 000 person years). Proteinuria greater than 1000 mg/24 hours developed in 28 patients (1%), hypertension in 371 patients (13.7%), and diabetes in 95 patients (3.6%). Therapeutic intervention-controlled protein was less than 1000 mg/24 hours, blood pressure was below 140/90 mm Hg, and glycemic control in 85% up to 15 years after onset. Creatinine clearance fell from 109.8 ± 22.3 mL/min per 1.73 m 2 predonation to 78 ± 17 at 1 year, 84 ± 19 at 5 years, and 70 ± 20 at 25 years. Comparison of 90 nondonor sibling and donor pairs showed significantly higher fasting glucose and hypertension in nondonors. Conclusions: Long-term follow-up of donors has demonstrated end-stage renal disease in 0.6% at 25 years. Regular follow-up identified new onset of disease and allowed interventions that may have prevented adverse outcomes. Abstract : The incidence of ESRD of living related kidney donors was 0.6% at 25 years in Pakistan. Nondonors show significantly higher fasting glucose and hypertension compared to donors. Regular follow-up identified new onset of disease and allowed interventions that may have prevented adverse outcomes.